The Role of Muslim Women as Content Creators: Building Islamic Communication Values - Sumanti, Elvi; Abdullah, Abdullah (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The development of communication technology has significantly transformed the way humans communicate and share information. Social media, as one of the new forms of internet-based media, has become an active platform for women, especially Muslim women, to act as users, content creators, and agents of social change. This paper examines the role of Muslim women as content creators in conveying Islamic values through social media, focusing on the analysis of Islamic communication principles applied.The study uses the TikTok account @anggi.22.4, owned by Cut Anggi, as a case study to identify how the produced content effectively communicates messages aligned with the principles of tabligh (conveying the truth), amar ma'ruf nahi munkar (encouraging good and preventing evil), and hikmah (wisdom). The findings demonstrate that a polite, simple approach rooted in Islamic values can have a positive impact on netizens, both Muslim and non-Muslim.This paper provides insights into how Muslim women as content creators can become effective agents of change through digital communication based on Islamic values, while also addressing the challenges of digital culture in the modern era.